A few remarks on the proposed amendment of the International Code of Zoological Nomenclature to expand and refine methods of publication - Carlos, Caio J.; Voisin, Jean-François (Zootaxa, 2009)
The purpose of the International Code of Zoological Nomenclature (hereafter ‘the Code’) is to promote nomenclatural stability. If the Rules are changed every tenth year or so, Zoological Nomenclature will have to adapt each time to the new rules, which will be a source of instability. Another thing will be that the taxonomists will have to consider each time under which edition of the Code nomenclatural acts will have been done, which will unnecessarily complicate his work, and will even be a cause of mistakes. We do not think that a new Code is necessary, for the moment at least.